2021
DOI: 10.3390/polym13203559
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Ca-Alginate/Chitosan Nanocomposite Loaded with Camptothecin

Abstract: The main aim of this study was to prepare antimicrobial nanocomposites consisting of alginate, chitosan, and camptothecin (CPT). CPT-loaded calcium alginate (Ca-Alg2) and calcium alginate/chitosan (Ca-Alg2-CH) nanomaterials were synthesized and characterized using infrared (IR) spectroscopy, X-ray diffraction (XRD), UV-Vis spectroscopy, and scanning electron microscopy (SEM). The antimicrobial activity and the genetic effects of Ca-Alg2/CPT and Ca-Alg2-CH/CPT nanomaterials on Staphylococcus aureus, Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Further, chemotherapeutic drugs (CPT) and CPT-LNP also demonstrated potential antibacterial properties in both dark and laser-treated conditions, and bacterial growth was reduced to approximately 50%. A similar report was also found in which CPT and CPT-based nanoformulation displayed potent antibacterial potential. , Alaghaz and the group also noted a similar finding regarding the antibacterial action of CPT . After being subjected to laser irradiation, the developed RB@CPT-LNP produced the most ROS, followed by RB, which is responsible for the greatest percentage of microbial cell death.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Further, chemotherapeutic drugs (CPT) and CPT-LNP also demonstrated potential antibacterial properties in both dark and laser-treated conditions, and bacterial growth was reduced to approximately 50%. A similar report was also found in which CPT and CPT-based nanoformulation displayed potent antibacterial potential. , Alaghaz and the group also noted a similar finding regarding the antibacterial action of CPT . After being subjected to laser irradiation, the developed RB@CPT-LNP produced the most ROS, followed by RB, which is responsible for the greatest percentage of microbial cell death.…”
Section: Resultssupporting
confidence: 72%
“…A similar report was also found in which CPT and CPT-based nanoformulation displayed potent antibacterial potential. 65,66 Alaghaz and the group also noted a similar finding regarding the antibacterial action of CPT. 44 After being subjected to laser irradiation, the developed RB@CPT-LNP produced the most ROS, followed by RB, which is responsible for the greatest percentage of microbial cell death.…”
Section: Resultssupporting
confidence: 55%
“…Florfenicol by Alginate/Chitosan nano carriers. [42] The formation of DOX-FLO@AgNPs nanostructures was also confirmed through the UV-Vis absorption spectra (Figure 4). FLO showed the absorption peak at 255 nm while DOX showed 2 absorption peaks at 270 and 350 nm.…”
Section: Chemistryselectmentioning
confidence: 75%
“…Furthermore, Al-Getahami and Al-Qasmi [131] have obtained important results when loading camptothecin into calcium alginate-chitosan nanocomposites. The authors reported enhanced inhibitory activity against Gram-negative bacteria, which could be explained by the induction of genetic effects.…”
Section: Antimicrobial Agentsmentioning
confidence: 99%